Diverse Bacterial Genes Modulate Plant Root Association by Beneficial Bacteria - Fernanda Plucani do Amaral (American Society for Microbiology, 2020)
ABSTRACT The plant rhizosphere harbors a diverse population of microorganisms, including beneficial plant growth-promoting bacteria (PGPB), that colonize plant roots and enhance growth and productivity. In order to specifically define bacterial traits that contribute to this beneficial interaction, we used high-throughput transposon mutagenesis sequencing (TnSeq) in two model root-bacterium systems associated with Setaria viridis: Azoarcus olearius DQS4T and Herbaspirillum seropedicae SmR1. This approach identified ∼100 significant genes for each bacterium that appeared to confer a competitive advantage for root colonization. Most of the genes identified specifically in A. olearius encoded metabolism functions, whereas genes identified in H. seropedicae were motility related, suggesting that each strain requires unique functions for competitive root colonization. Genes were experimentally validated by site-directed mutagenesis, followed by inoculation of the mutated bacteria onto S. viridis roots individually, as well as in competition with the wild-type strain. The results identify key bacterial functions involved in iron uptake, polyhydroxybutyrate metabolism, and regulation of aromatic metabolism as important for root colonization. The hope is that by improving our understanding of the molecular mechanisms used by PGPB to colonize plants, we can increase the adoption of these bacteria in agriculture to improve the sustainability of modern cropping systems. IMPORTANCE There is growing interest in the use of associative, plant growth-promoting bacteria (PGPB) as biofertilizers to serve as a sustainable alternative for agriculture application. While a variety of mechanisms have been proposed to explain bacterial plant growth promotion, the molecular details of this process remain unclear. The current research supports the idea that PGPB use in agriculture will be promoted by gaining more knowledge as to how these bacteria colonize plants, promote growth, and do so consistently. Specifically, the research seeks to identify those bacterial genes involved in the ability of two, PGPB strains, Azoarcus olearius and Herbaspirillum seropedicae, to colonize the roots of the C4 model grass Setaria viridis. Applying a transposon mutagenesis (TnSeq) approach, we assigned phenotypes and function to genes that affect bacterial competitiveness during root colonization. The results suggest that each bacterial strain requires unique functions for root colonization but also suggests that a few, critical functions are needed by both bacteria, pointing to some common mechanisms. The hope is that such information can be exploited to improve the use and performance of PGPB in agriculture.